2022
DOI: 10.3390/agriculture12121980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Chemical Features on Aromatic Profile of V. vinifera cv. Corvina Grapes and Wines: A Study-Case in Valpolicella Area (Italy) in a Calcareous and Non-Calcareous Soil

Abstract: In the Valpolicella area (Verona, Italy) one of the most important Italian wines is being produced: Amarone, predominately made by Vitis vinifera cv. Corvina. This wine is subjected to a specific postharvest process, namely, withering, which aims to increase alcohol content and/or high residual sugars while retaining richness in aromas and organoleptic compounds. In accordance with guidelines and strict Amarone protocol set by the Consorzio of Amarone-Valpolicella, withering must be carried out by setting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In contrast, acidity levels, encompassing both total and malic acid, reached their peak in the treated group, subsequently influencing the pH. This observed pattern aligns with established findings in the literature, where salt stress typically leads to a reduced sugar content, resulting in increased acidity and decreased pH [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, acidity levels, encompassing both total and malic acid, reached their peak in the treated group, subsequently influencing the pH. This observed pattern aligns with established findings in the literature, where salt stress typically leads to a reduced sugar content, resulting in increased acidity and decreased pH [37].…”
Section: Discussionsupporting
confidence: 88%
“…Also, this genus plays a role in the microbiota of grape berries, influencing the fermentation process during winemaking. The presence of Bacillus in the grape microbiota in fact was reported to contribute to the distinctive microbial fingerprint of a vineyard, adding to the complexity and uniqueness of the resulting wine [37]. For instance, Bacillus could inhibit the malolactic bacterium, Oenococcus oeni, responsible for malolactic fermentation [68].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other soil chemical properties, significant associations between them and wine's organoleptic characteristics have been found [353]. For example, Tomasi et al [358] reported the effect of high limestone content on obtaining higher aromatic wines, and Arnó et al [319] found that high calcium carbonate and pH lead to Mn deficit and, consequently, grapes low in phenolic contents.…”
Section: The Soil Environment and The Terroir Expressionmentioning
confidence: 99%
“…However, EU exports didn't change in recent years, due to transport disruption in countries in the Southern hemisphere and North America [6]. In Italy, wine production (including grape juice) is equal to 48.2 million hectolitres on a vineyard area of approximately 621.9 thousand hectares [8]. As far as Italy is concerned, there has been a significant rise in volume exports, without the accompanying rise in value, similar to what occurred for France.…”
Section: Introductionmentioning
confidence: 99%